1972
DOI: 10.1073/pnas.69.10.3004
|View full text |Cite
|
Sign up to set email alerts
|

An Adenosine Triphosphate-Phosphate Exchange Catalyzed by a Soluble Enzyme Couple Inhibited by Uncouplers of Oxidative Phosphorylation

Abstract: The sulfenic acid form of glyceraldehyde-3-phosphate dehydrogenase (EC 1.2.1.12), which is an acyl phosphatase, will catalyze an acetyl phosphate-Pi exchange reaction. This exchange reaction is reversibly inhibited by the uncouplers of oxidative phosphorylation, 2,4-dinitrophenol, m-Cl carbonylcyanide-phenylhydrazone, pentachlorophenol, and 5-chloro-3-tert-butyl-2'-chloro-4'-nitrosalicylanalide, and is irreversibly inhibited by cyanide and dicumarol. An ATP-Pi exchange reaction similar to that catalyzed by mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…A considerable proportion of the soluble ATPase activity could thus be due to these 'nothing kinase' activities. A further possible source may be sulphenyl glyceraldehyde phosphate dehydrogenase, which undoubtedly was present, acting in the way described by Allison & Benitez (1972).…”
Section: Discussionmentioning
confidence: 98%
“…A considerable proportion of the soluble ATPase activity could thus be due to these 'nothing kinase' activities. A further possible source may be sulphenyl glyceraldehyde phosphate dehydrogenase, which undoubtedly was present, acting in the way described by Allison & Benitez (1972).…”
Section: Discussionmentioning
confidence: 98%
“…The discovery that the specific conversion of Cys-149 in GAPDH to corresponding sulfenic acid converts the enzyme from dehydrogenase to an acyl phosphatase was probably the first to hint at a biological role for protein sulfenic acid [68,72,73]. Another study demonstrated oxidation of the lone free thiol in albumin upon incubation with xanthine oxidase [74].…”
Section: Sulfenic Acids In Proteinsmentioning
confidence: 99%
“…However, there is evidence that some protein sulfenates are sufficiently stable to operate as post-translational regulators of function in some proteins. For example, it is established that a number of transcription factors form regulatory sulfenic acids, including OxyR, OhrR, and Yap1 (9, 12, 13, 28 -30) Other proteins that form sulfenates include members of the NAD(P)H:disulfide reductase family, tyrosine phosphatases, peroxidases, and methionine sulfoxide reductases However, most of these are bacterial proteins, although some mammalian proteins have been identified (14,(31)(32)(33).…”
Section: Fig 8 a Western Blot Obtained From Isolated Hearts That Hmentioning
confidence: 99%